Abnormal behavior of total ozone over Indian region during 1991-98 - LONDHE, A. L.; PATIL, S. D.; KUMARI, B. PADMA; JADHAV, D. B. (MAUSAM, 2003)
The total column ozone variation over India has been studied using monthly mean ozone for the period of 18 years from 1981 to 1998, which were collected with Dobson Spectrophotometer at four Indian stations, New Delhi (28° N), Varanasi (24° N), Pune (18° N), and Kodaikanal (10° N). The effect of atmospheric phenomena like Quasi Biennial Oscillation (QBO), solar cycle and volcanic eruptions (El Chichon of 1982, Mt. Pinatubo of 1991) on ozone variations has also been explored in this paper. The results of the analysis has shown that the ozone variations in the tropical region seem to have mostly caused by the equatorial QBO in zonal wind at lower stratosphere and solar cycle. During the period 1981-90, there is no much year to year variability in total ozone, whereas during the period 1991-98, much variability is observed between year to year. The total ozone is decreased from 1991 to 1993 and later started recovering. The ozone anomalies calculated for the period 1981-98 showed positive anomaly for the period 1981-90 and negative anomaly for the period 1991-98. Though the contribution of QBO and solar cycle to total ozone for the two different periods of 1981-90 and 1991-98 is almost same, the total ozone amounts for the later period are lower. These lower ozone amounts may be attributed to the Mt. Pinatubo volcanic eruption.